The legal implications of 'Fatwā Shopping' in the Islamic finance industry: Problems, perceptions and prospects - Oseni, Umar Aimhanosi; Ahmad, Abu Umar Faruq; Hassan, Mohammad Kabir (Brill Academic Publishers, 2016)
This article examines the occurrence and legal implications of ‘fatwā shopping’ in the Islamic finance industry and the need to put the proper legal mechanisms in place to regulate the phenomenon. It provides a case study of the existing legal restrictions in some jurisdictions with a centralised Sharīʿah Supervisory Board at the national level such as in Malaysia. As a preliminary review of the implications of ‘fatwā shopping’ in the industry, this study examines the consequential problems, current perceptions and prospects of such practice. The study finds that instances of ‘fatwā shopping’ are common in cross-border Islamic finance transactions such as cross-border ṣukūk transactions where there is less regulation.